2010
DOI: 10.1093/fampra/cmq057
|View full text |Cite
|
Sign up to set email alerts
|

Delays in response and triage times reduce patient satisfaction and enablement after using out-of-hours services

Abstract: giving users more time to discuss their illness in consultations may enhance satisfaction and enablement but this may be resource intensive. More simple interventions to improve access by quicker response and triage, and keeping users informed of waiting times, could also serve to increase satisfaction and ultimately impact on their enablement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…27 Generally, patients have found telephone consultations with GPs and nurses to be acceptable, 11,13,70,[73][74][75] although one systematic review included primary studies that, overall, showed patient dissatisfaction with telephone consultations. 76 Our findings are consistent with past research with respect to GPT.…”
Section: Patient Experiencementioning
confidence: 99%
“…27 Generally, patients have found telephone consultations with GPs and nurses to be acceptable, 11,13,70,[73][74][75] although one systematic review included primary studies that, overall, showed patient dissatisfaction with telephone consultations. 76 Our findings are consistent with past research with respect to GPT.…”
Section: Patient Experiencementioning
confidence: 99%
“…The involvement of a supervising PCP at the call center (telephone PCP), computerized decision support systems, electronic patient records, and other organizational factors might influence the number of follow-up contacts. 3 Previous research showed that delays in answering calls or calling back and shorter consultations were associated with a more negative evaluation, 18 and the presence of a telephone PCP seemed to be related to a more positive evaluation of nurse telephone consultation. 8,19 Better insight into determinants of follow-up contacts could provide guidance for decision makers in their efforts to improve the efficiency of out-of-hours care.…”
mentioning
confidence: 99%
“…Eight publications described patient satisfaction after the consultation provided by the teleconsultation centers 17,19,25,26,39,4244. Other settings include: the management of same-day appointments;6 the provision of teleconsultation services by physicians outside of specialized telemedicine institutions;19,23,45,46 maritime telemedicine;30 prison medicine;24 and teledermatology services 23.…”
Section: Resultsmentioning
confidence: 99%
“…The timing of instrument administration varied considerably across the studies. In addition, 16 publications (52%) reported the distribution of the questionnaires within 7 days of the consultation,6,1924,27,3234,36,37,4042 seven studies (23%) between 14–28 days,17,18,26,28,38,39,44 and one publication (3%) reported a latency of 4–16 months 30. Also, seven (23%) studies did not report on the timing of the instrument’s administration (Table 1).…”
Section: Resultsmentioning
confidence: 99%